1969 vs 2014 : 45 ans d’enseignement du cinéma et de l’audiovisuel sur trois générations - Michel Marie (Mise au Point)
This article’s aim is to provide an exhaustive view of nearly half a century of university education on cinema and audiovisual studies.The contents of this education have been intertwined with the activities of university research and larger disciplinary fields. The modes of reference have evolved decade by decade, and now concern three generations of teachers-researchers. If the emerging period seemed dominated by a few in vogue disciplines or thought processes as semiology or structuralism, the ones that followed saw other models appear as with philosophy, cognitivism, or figurative analysis. But most social sciences, as history, economy, sociology, cultural studies and a few others have brought their methodology and disciplinary modes to cinema studies, therefore enriching the field and broadening the knowledge of cinema’s art, its sociology and history, and audiovisual medias in the digital era.